Studi Kecukupan Asupan Energi Ketika Masa Puasa - Y. Touvan Juni Samodra; Kurniawan Hidayatulloh; Handayani Handayani; Yulia Emelda; Subarjo Subarjo (Journal of Sport Coaching and Physical Education, 2024)
This study aims to determine the macronutrient intake patterns of sports students who fast. Fasting is a must for Muslims, including those who are still actively participating in training and studying. Fasting conditions will cause very big changes related to changes in eating times. What was originally free became limited only from Maghrib until before Fajr at the specified time. Arranging to prevent nutritional deficiencies and lack of sleep is very important. The research method is a survey with food activity recall as an instrument. Respondents were 26 students who recorded and filled in independently. Training was held to fill in the nutrition survey program first and a simulation was held. Analysis Data was entered into the nutrie survey program for analysis. The recommended energy adequacy will be the main discussion. The results of the research show that students' energy adequacy is very low, only an average of 57%. Based on the results of this research, for students who are still athletes, this lack of energy intake deserves attention, as well as for students who are just active, a lack of energy intake for a long time will have a negative effect on activity.